Remarkable discoveries in the long-neglected and Peruvian-endemic genus Machaerophorus (Brassicaceae) - Al-Shehbaz, Ihsan A.; Cano, Asunción; Cueva Manchego, Marco Antonio; Salariato, Diego L. (Phytotaxa, 2018)
The Peruvian genus Machaerophorus has long been reduced to synonymy of several genera of various tribes. With the discovery of two new species described below, M. arequipa and M. laticarpus, and availability of material for molecular phylogenetic studies, the genus is reinstated for the first time in over a century and included within the South American “Cremolobeae-Eudemeae-Schizopetaleae” clade.